Prolonged elevated body mass index in preschool children after the Great East Japan Earthquake - Isojima, Tsuyoshi; Yokoya, Susumu; Ono, Atsushi; Kato, Noriko; Tanaka, Toshiaki; Yokomichi, Hiroshi; Yamagata, Zentaro; Tanaka, Soichiro; Matsubara, Hiroko; Ishikuro, Mami; Kikuya, Masahiro; Chida, Shoichi; et al. (Pediatrics international, 2017)
Background The Great East Japan Earthquake followed by tsunamis and the Fukushima Daiichi Nuclear Power Plant (NPP) accident caused catastrophic damage. The effects of the disaster on the growth of affected children are of great concern but remain unknown. Methods The subject group was derived from two Japanese nationwide retrospective cohorts (historical control and exposure groups, respectively). The exposure group experienced the disaster at 47–59 months of age. We analyzed longitudinal changes in standard deviation score (SDS) for height and body mass index (BMI) using normal Japanese children's standards. Moreover, we analyzed the details of the affected children in Fukushima using Fukushima‐specific growth charts established with the historical control data to clarify any indirect effect of the disaster on growth. Results Affected children in Fukushima had significantly higher BMI SDS than the historical control group (difference, 0.13; 95% CI: 0.044–0.21, P = 0.0029) and the regional controls (difference, 0.14; 95% CI: 0.074–0.20, P < 0.0001) 1.5 years after the disaster. Similar sustained increases in BMI SDS were also found with Fukushima‐specific growth charts, but the phenomenon was detected only in boys. Notably, the BMI SDS of affected children who lived near the NPP had been increasing after the disaster, whereas those in distant areas had not changed. In contrast, height SDS had not changed throughout the analysis. Conclusions Prolonged elevated BMI SDS was detected only in affected children in Fukushima. This phenomenon may be explained by an indirect effect of the NPP accident.